Developing adaptability in future professionals in the realm of adaptive physical education - Nekhoroshikh N.A. ,; Voishcheva E.L. ,; Zakharova M.A. ,; Larina I.B. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the educational requirements and methods for developing the adaptability of a future professional in the field of adaptive physical education. Methods and structure of the study. The success of the technology for cultivating professional adaptability in future professionals in the field of adaptive physical education is contingent upon the fulfillment of certain pedagogical requirements: the implementation of a specially designed program for fostering professional adaptability within the framework of the educational process for training professionals in adaptive physical education; the integration of dynamic teaching and nurturing methods and techniques into the educational process, such as workshops, group discussions, strategic planning, scenario analysis, case studies, and more; ongoing assessment of professional adaptability development; and considering the unique characteristics of students when devising strategies for personal professional growth. To validate the theoretical findings, a practical investigation was carried out, involving 42 students enrolled in the Bachelor's program 49.03.02 «Physical Education for Individuals with Disabilities» at the I.A. Bunin Yelets State University. Results and conclusions. The implementation of a practical-oriented curriculum, underpinned by specific pedagogical principles, within the context of active learning methods, not only enhances the overall quality of these professionals' education, but also equips them with the skills necessary to thrive in the dynamic professional landscape of the future, where the demands for specialists are constantly evolving.